Analysis of Acrylamide in Dried Blood Spots of Lung Cancer Patients by Ultrahigh-Performance Liquid Chromatography Tandem Mass Spectrometry - Yahdiana Harahap; Camilla Elysia; Zenshiny Starlin; Achmad Mulawarman Jayusman (International Journal of Analytical Chemistry)
Acrylamide (AA) is a carcinogenic substance found in food, cigarette smoke and in an environment exposed to acrylamide. This study aims to analyze AA levels in dried blood spot (DBS) samples of lung cancer patients with smoking record, without smoking record, and also in the negative blank. Analysis of AA levels was determined by liquid chromatography tandem mass spectrometry (LC-MS/MS) and DBS extraction using protein precipitation techniques. Mass detection was done using positive electron spray ionization (ESI) and multiple reaction monitoring (MRM) type with m/z values of 71.99 > 55.23 for acrylamide and m/z 260.16 > 116.04 for propranolol as the internal standard. AA levels in lung cancer patients with smoking record is in the range of 4.670 μg/mL to 11.986 μg/mL. AA levels in lung cancer patients without smoking record is in the range of 2.041 μg/mL to 12.702 μg/mL. Data on AA levels on negative blanks is in the range of 2.72 μg/mL to 3.51 μg/mL. The results of the independent sample t-test (p>0.05) showed that AA levels in patients with smoking record and those without smoking record did not differ significantly. Then, the Mann-Whitney test was performed between the lung cancer group and the negative blank group and a significant difference was found between the two groups (p<0.05).